Evaluating scientific publications in the field of sports management: a bibliometric study based on the Web of Science database - Muzaffer Toprak Keskin; Nurten Ulusay; Şevket Cihat ÖZER; Münevver Ulusay (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to evaluate the research in sports management from a broader perspective, considering its scope, quality and impact. It uses bibliometric analysis, a method that quantifies and assesses academic studies, to reveal the trends, topics, methods and gaps in this field. Bibliometric analysis applies mathematical and statistical methods to analyse scientific activities and it can show the trends, hot topics, relationships and collaborations among countries, regions, institutions, research fields and authors by examining academic research conducted in various countries, universities and publications. The data for this study were collected from the Web of Science (WoS) database, which was chosen for the literature review because it is a more authoritative and widespread source than other databases and it offers high-quality journals and a complete data structure for bibliometric analysis. The search in the WoS database was conducted using keywords related to sports management, such as “sports economics, sports industry, financial sports, sports and economy, sports organization, sports management, sports media, sports technology, sports innovation, sports policy, sponsorship and sports clubs, sports business” and so on. The data were analysed with RStudio program and bibliometric analysis was performed. The results show that the number of studies in sports management has increased continuously from 1991 to 2023. Moreover, the contents of the studies in this field have changed over time. For instance, while the word «sport» was more common in the earlier years, the word «sports» has become more prevalent in recent years. This indicates that sport has evolved into a multidisciplinary concept that encompasses different sports branches. However, most of the studies in sports management do not adequately address the economic dimension of sports management. Therefore, there is a need for more and more comprehensive scientific publications in this field. The findings suggest that the research in this field is growing over time, but there are still many research gaps in sports economics.